Pelatihan Analisis Usaha Pada Klaster Batik Semarang - Sri Yuni Widowati; Wyati Saddewisasi; Teguh Ariefiantoro; Aprih Santoso (IAI Darussalam, 2019)
The purpose of the training is to increase understanding and knowledge of planning through business analysis, so that batik business is expected to increasingly be able to increase the profits of entrepreneurs in the batik cluster. Training implementation methods are: counseling methods (lectures, questions and answers) and discussions between participants. Evaluation of training activities is carried out with pre-test and post-test. The results of the training are that participants are able to know and understand business development techniques; able to know and understand about how to make a business feasibility study and measure strengths, weaknesses, opportunities, and business threats (SWOT Analysis). This can be seen from the pre-test results distributed by the training team. The conclusions of this training include the members of the batik cluster who have been able to increase knowledge about business development techniques and can conduct business feasibility studies, measure strengths, weaknesses, opportunities, and business threats (SWOT Analysis) as well as increasing motivation to run their businesses.